STUDY OF RELATIVISTIC ENERGY 207Pb PROJECTILE FRAGMENTATION ON HEAVY TARGETS - Sher, G.; Shahzad, M. I.; Manzoor, S.; Rana, M. A.; Yasin, Z. (The Nucleus, 2010)
Fragmentation of 158 A GeV 207Pb projectiles is studied on Bi, Pb, Cu and Al targets using CR-39 nuclear track detectors. Stacks containing detectors and targets were exposed at SPS beam facility of CERN. After chemically etching, detectors were scanned with an optical microscope. Lengths of etched cones produced as a result of beam ions and the fragments in the detectors have been measured. The charge resolution (σZ) achieved by this technique in the charge region 63 < Z < 82 is ~ 0.3e – 0.2e. The total charge-changing cross sections have been determined using the statistics of etched cone heights corresponding to the projectile ions and their nuclear fragments. Measured total charge-changing cross sections are compared to the corresponding calculations with semi-empirical models and predictions of the FLUKA code. The dependence of total cross sections on the projectile and target mass is also described.